Carotid Stiffness Assessment With Ultrafast Ultrasound Imaging in Case of Bicuspid Aortic Valve - Goudot, Guillaume; Mirault, Tristan; Khider, Lina; Pedreira, Olivier; Cheng, Charles; Porée, Jonathan; Gruest, Maxime; Jeunemaître, Xavier; Pernot, Mathieu; Messas, Emmanuel (Frontiers in Physiology, 2019)
Aims: To compare the carotid stiffness and flow parameters by ultrafast ultrasound imaging (UF), in bicuspid aortic valve (BAV) patients to first-degree relatives (controls). Methods: BAV patients (n=92) and controls (n=48) were consecutively included at a reference center for BAV. Aortic valve and ascending aorta were evaluated by echocardiography. Common carotid arteries were evaluated by UF with a linear probe. A high frame rate (2,000 frames/s) was used to measure the pulse wave velocity (PWV). The arterial diameter change over the cardiac cycle was obtained by UF-Doppler imaging. This allowed us to measure the distensibility and the maximal rate of systolic distension (MRSD). The wall shear stress (WSS) was measured based on the same acquisitions, by analysing blood flow velocities close to the carotid walls. Results: BAV patients had significantly larger aortic diameters (p<0.001) at the Valsalva sinus and at the tubular ascending aorta but no larger carotid diameters. No significant differences were found in carotid stiffness parameters (distensibility, MRSD and PWV), even though these patients had a higher aortic stiffness. Carotid stiffness correlated linearly with age and similar slopes were obtained for BAV patients and controls. No difference in carotid WSS was found between BAV patients and controls. Conclusion: Our results clearly show that the carotid stiffness and flow parameters are not altered in case of BAV compared with controls.